Botanical fungicides in the control of soybean leaf diseases / Fungicidas botânicos no controle de doenças foliares na soja - Dalcin, Mateus Sunti (2021)
The soybean cultivation (Glycine max (L.) Merrill) is responsible for the highest pesticides use in agriculture in Brazil. There is an environmental and social need to reduce the use of these substances in crops. The alternative products applied in agriculture such as plant extracts and essential oils, becomes necessary and indispensable, mainly in disease control. Among the plants studied, the Noni (Morinda citrifolia L.), has stood out in some studies, where relevant fungitoxic results have been demonstrated, however, there are still few works that prove its viability in the diseases management in field. Thus, this work aimed to evaluate the soybean diseases alternative control through the aqueous extracts and noni essential oil application, in plantings high and low disease pressure. Two field experiments were implemented, with soybean culture, evaluating leaf, fruit aqueous extract and noni essential oil as a fungicidal action. Foliar application of noni extracts and essential oil did not differ from fungicide in Asian Rust and Anthracnose control, in the 2016/17 crop, in both experiments. Soybean productivity was similar in treatments that received leaf extract (1748,8 Kg ha-1), essential oil (1762,5 Kg ha-1) and fungicides (2031,7 Kg ha-1). Where there was no large disease pressure all agronomic characteristics were equivalent, regardless of treatment.